KAJIAN KRITIS TERHADAP DINAMIKA PENDIDIKAN ISLAM PADA MASA BANI UMAYYAH - Yafi, Salman; Azmiyah; Olivia; Zulmuqim; Masyhudi, Fauza (PT. Hafasy Dwi Nawasena, 2023)
Islam and Islamic education are a unity that has a close relationship with each other in Islamic history. Since the beginning of Islamic history, the history of Islamic education has also begun. Education itself is something that is continuous in history and often produces dynamics that go up and down. The Bani Umayyah period is one of the constituent components of the history of Islamic education, which at that time had its own educational dynamics so that it was known as the incubation period. The purpose of this research is to find out the dynamics of education during the Umayyad period. This research is a literature research and uses historical research methods. The results of the research are in the form of factors that hinder the dynamics of education, government policies regarding education, and natural factors that cause the dynamics of education during the Umayyah period to continue.